How churches grow in an urban world - Dubose, Francis M. (Nashville : Broadman Press, 1978)
History, theology, and strategy of growth in all kinds of city churches.--dust cover blurb.
Includes index.
Bibliography: p. 172-175.
Keywords: Church growth; City churches